Genome of Labrenzia sp. PHM005 Reveals a Complete and Active Trans-AT PKS Gene Cluster for the Biosynthesis of Labrenzin - Kačar, Dina; Schleissner, Carmen; Cañedo, Librada M.; Rodríguez, Pilar; de la Calle, Fernando; Galán, Beatriz; García, José Luis (Frontiers in Microbiology, 2019)
The complete genome of the strain Labrenzia sp. PHM005, a free-living producer of a pederin analog 18-O-demethyl pederin, hereinafter labrenzin, has been sequenced. This strain contains two replicons comprising a circular chromosome of 6,167,349 bp and a circular plasmid (named p1BIR) of 19,450 bp. A putative gene cluster responsible for the synthesis of labrenzin (lab cluster) has been identified showing that it encodes a trans-AT mixed type PKS/NRPS biosynthetic pathway that is responsible for the synthesis of pederin and possibly an onnamide analog. The putative boundaries of the lab gene cluster were determined by genetic comparisons with other related strains, suggesting that the cluster consists of a 79-kb region comprising 3 genes encoding multidomain hybrid polyketide synthase/nonribosomal peptide synthetase (PKS/NRPS) proteins (PKS4, PKS/NRPS13, and PKS/NRPS15), and 16 auxiliary enzymes. Transcriptomic analyses suggest that all the genes of the cluster are expressed in our culture conditions (i.e., in minimal medium in the absence of any specific inducer) at detectable levels. We have developed genetic tools to facilitate the manipulation of this strain and the functional characterization of the cluster genes. We have created a site-directed mutant unable to produce pederin, demonstrating experimentally for the first time the role of the cluster in the synthesis of pederin. This work paves the way to unravel the clues of the biosynthesis of pederin family compounds and opens the door to modify and overproduce these anticancer drugs for industrial and pharmaceutical purposes.